PENGARUH LABA BERSIH DAN ARUS KAS OPERASI TERHADAP KEBIJAKAN DIVIDEN DENGAN UKURAN PERUSAHAAN SEBAGAI MODERASI PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI PERIODE 2021 - 2023 - Pirmansyah, Pirmansyah; Wahyu, Wadri; Oktaviani, Wulan; Helmiati, Helmiati; Munika, Rani (Komunitas Manajemen Kompetitif, 2024)
This research aims to examine the influence of net profit and operating cash flow on dividend policy with company size as moderation in LQ45 companies listed on the IDX for the 2021 - 2023 period. This research uses quantitative methods with secondary data as the source. The sample in this study was 22 using the positive sampling method. The data analysis technique used is moderation analysis using the Smart PLS test tool. The research results show that partially, net profit and company size have a significant influence on dividend policy, while operating cash flow does not have a significant influence on dividend policy, while company size is unable to moderate net profit and cash flow on dividend policy.